Analysis of Tax Service Quality and Taxpayer Satisfaction During the Covid-19 Pandemic at the Pratama Tax Office Cileungsi, Bogor, West Java, Indonesia - Ma'ruf, Solehan; Budiati, Ayuning; Wibowo, Soesilo (Yayasan Sinergi Kawula Muda, 2023)
Service is the effort to achieve public service quality for taxpayers, all services are provided through Integrated Service Centers (ISC) at each Tax Service Office (TSO) and at Tax Service, Counseling, and Consultation Offices (TSCTCO) throughout Indonesia's tax areas, and taxpayers' satisfaction with the services provided by KPP Pratama Cileungsi, as well as the initiatives undertaken and planned by KPP Pratama Cileungsi to improve service quality during the Covid-19 pandemic. This study identified several issues: 1) Taxpayer satisfaction with tax services at the Tax Service Office KPP Pratama Cileungsi during the Covid-19 pandemic, 2) Efforts made by the Tax Service Office KPP Pratama Cileungsi to enhance the quality of tax services during the Covid-19 pandemic. The research method employed a descriptive qualitative approach conducted in a natural setting, with data collected using interview guidelines and documentation. The research informants included strategic taxpayers, tax volunteers, and employees of KPP Pratama Cileungsi. Data analysis encompassed activities such as data reduction, presentation, and drawing conclusions/verification. The results of this study revealed that tax class activities are part of cooperation with the district government to ensure that the public is aware of and utilizes these tax classes as a means of learning and increasing tax obligation awareness. Creating or re-sharing tax education content through a dedicated YouTube channel serves as a contemporary education platform with easy access anytime and anywhere for taxpayers, given the extensive jurisdiction of KPP Pratama Cileungsi. This YouTube channel should be promoted through village government devices to be known by the wider community, especially in the jurisdiction area of KPP Pratama Cileungsi.